A finding of maintained cryonotothenioid nesting sites in the Western Weddell Sea - Russell B. Connelly; Lucy C. Woodall; Alex David Rogers; Michelle L. Taylor (Frontiers in Marine Science, 2025)
The Weddell Sea is one of Earth’s most remote and least studied regions. The region around the Larsen C Ice shelf has been largely inaccessible because of its remoteness, extreme cold, rough seas, ice cover, and deep waters. This study documents the first discovery of maintained nesting sites of Lindbergichthys nudifrons (yellowfin notie) in the western Weddell Sea. Nesting sites were found at all locations surveyed during the Weddell Sea Expedition 2019 onboard the SA Agulhas II using the remotely operated vehicle, Lassie . Unlike previous studies, no significant differences in localised water temperature were detected between nesting sites and surrounding waters, except at one site. Novel nesting patterns, groups of nests close to each other, were discernible throughout the video footage; These patterns are thought to have evolved as a form of group predation protection behaviour. These findings provide critical evidence of unique, structured breeding habitats, fulfilling key criteria for the designation of Vulnerable Marine Ecosystems and strengthening the case for the proposed Weddell Sea Marine Protected Area.